The ‘New Man’ Character and an Integrative Image of the Male and the Female World in Chimamanda Ngozi Adichie’s 'Americanah' (Mwanga wa Lugha, 2022)
This paper examines the making of ‘new man’ character in Adichie’s Americannah and  discusses how such a molded man integrates himself in society and deals with other  gendered worlds. The discussion shows how much Adichie in the representation of ‘new  man’ character in her novel rejects the naturalization of the unchangeability of the male  subject by dramatizing how much the male’s enactment of masculine-self is contingent  on the orientation one gets. In this paper, I argue that Adichie’s representation of progressive ‘new man’ character in her novel not only serves as a role model for ideal progressive masculinity, but also re-invents a space necessary for a progressive female character to belong in hetero-patriarchal setting of the novel—the disavow of the normalized good womanhood made by a woman’s performance of silence and submissiveness. Indeed, the representation of progressive ‘new man’ in Americannah is treated in this paper as a womanist endeavor of creating an integrative Africa which accommodates both the enlightened men and enlightened women in the formation of ungendered relationships.